Risk of Postoperative Thromboembolism in Men Undergoing Urological Prosthetic Surgery: An Assessment of 21, 413 Men. Issue 4 (10th October 2022) - Hebert, Kevin J.; Matta, Rano; Horns, Joshua J.; Paudel, Niraj; Das, Rupam; Kohler, Tobias S.; Pastuszak, Alexander W.; McCormick, Benjamin J.; Hotaling, James M.; Myers, Jeremy B.
Abstract : Purpose: We assessed venous thromboembolism (VTE) and associated risk factors following artificial urinary sphincter (AUS) and inflatable penile prosthesis (IPP) surgery. Materials and Methods: Using IBM® MarketScan, a commercial claims database, patients undergoing AUS and IPP surgery were identified using CPT® and ICD (International Classification of Diseases)-10 procedure codes between 2008 and 2017. ICD-9 and -10 codes were used to identify health care visits associated with lower extremity deep vein thrombosis (DVT) and pulmonary embolism (PE) within 90 days of surgery. Covariates were assessed using a multivariable model to determine association with outcome of DVT and/or PE. Results: A total of 21, 413 men underwent AUS (4, 870) or IPP (16, 543) surgery between 2008 and 2017 with a median age of 62 years and 68 years, respectively. DVT and PE events following AUS and IPP surgery occurred in 1.54% and 1.04%, respectively. A history of varicose veins (HR 2.76; 95% CI 1.11–6.79), prior history of DVT (HR 13.65; 95% CI 7.4–25.19), or PE (HR 7.65; 95% CI 4.01–14.6) in those undergoing AUS surgery was highly associated with development of postoperative VTE. Likewise, prior history of DVT (HR 12.6; 95% CI 7.99–19.93) and PE (HR 8.9; 95% CI 5.6–14.13) was strongly associated with a VTE event following IPP surgery. Conclusions: In a large cohort of men undergoing AUS and IPP surgery, 1.54% and 1.04% of men experienced a VTE event within 90 days of surgery, respectively. Prior history of varicose veins, DVT, and PE was associated with an increased likelihood of developing a postoperative DVT or PE.